The Next Middle East Crisis Will Start If This Man Dies - Rubin, Michael (Business Insider, 2014)
The 74-year-old sultan has left no clear successor.
Keywords: Vie politique -- Oman -- 1970-2020

Oman: Will the Imamate Return? - Katz, Mark N. (Travels and Observations, 2014)
Some twenty years ago, I wrote up the following notes for myself after reading John C. Wilkinson’s The Imamate Tradition of Oman (Cambridge University Press, 1987): While Omanis are virtually all M…
Keywords: Vie politique -- Oman -- 1970-2020

Histoire : à Oman, le roi se meurt - Saint-Périer, Laurent de (Jeune Afrique (site web), 2014)
La maladie dont souffre l’atypique sultan Qabous pose la question de la succession, qui s’annonce d’autant plus délicate que le souverain s’est façonné un État sur mesure et n’a pas d’héritier. – Jeune Afrique
Keywords: Vie politique -- Oman -- 1970-2020

Succession incertaine à Oman - Qui remplacera le sultan Qabous ? - Valeri, Marc (Orient XXI, 2014)
Oman a servi d’intermédiaire entre les États-Unis et l’Iran et joue un rôle diplomatique actif dans la région. D’où l’inquiétude — partagée par la population — que (...)
Keywords: Vie politique -- Oman -- 1970-2020

America and Oman: The Context for Two Nearly Centuries of Relations - Peterson, John E. (2014)
Keywords: Vie politique -- Oman -- 1970-2020

Quel avenir pour le Sultanat d'Oman ? - Vagile, Juliette (Aujourd'hui la Turquie, 2014)
Les rumeurs de cancer et la raréfaction des apparitions du Sultan d’Oman inquiètent les citoyens de son pays : Qabous ben Saïd, n’ayant pas d’enfant, n’a effectivement pas de descendance directe, …
Keywords: Vie politique -- Oman -- 1970-2020

Oman’s mediatory efforts in regional crises - Valeri, Marc (Noref Expert Analysis, 2014)
Oman’s role in facilitating the conclusion of the Iran-P5+1 nuclear deal in November 2013 and its announcement a few weeks later that it would not join a proposed Gulf union can be understood within a recent history of conciliatory efforts intended to promote negotiated solutions to regional crises. Oman has always perceived political instability in the Gulf and West Asia as a factor threatening the country’s own internal stability. This perception of political vulnerability also explains the sultanate’s determination to prevent foreign actors from interfering in its internal affairs. The price for this independent foreign policy towards its neighbours has been the country’s unquestioned political and military dependence on Britain and the U.S. Given Oman’s strategic importance to the security of the entire Gulf, controlling as it does the Strait of Hormuz, through which approximately one-third of the world’s seaborne trade in crude petroleum passed in 2013, Britain and the U.S. have shared Muscat’s aversion for any disruption of its internal status quo and wish to prevent any contamination of Omani territory by unwanted foreign influence.
Keywords: Vie politique -- Oman -- 1970-2020

Oman: Quo vadis Märchensultanat? - Richter, Thomas (Giga, 2014)
Keywords: Vie politique -- Oman -- 1970-2020

Muscat as a Port City - Peterson, John E. (The Gulf in Modern Times: Peoples, Ports and History, 2014)
Keywords: Vie politique -- Oman -- 1970-2020

The Omani Pursuit of a Large Peninsula Shield Force: A Case Study of a Small State's Search for Security - Mason, Robert (British Journal of Middle Eastern Studies, 2014)
After the failure of a small Peninsula Shield Force (PSF) to protect Kuwait in the lead up to the Gulf War in 1991, Sultan Qaboos, the ruler of Oman, proposed to the Gulf Cooperation Council (GCC) that it develop a large-standing army of 100,000 troops. Although Oman was not wholly successful in achieving its objective during the main negotiation period up to 1995, it did manage to contribute to small shifts in GCC security policy during periods of conﬂict. Nevertheless, it took the Arab Uprisings in 2011 to achieve a fundamental re-orientation of GCC security policy which favoured higher numbers of PSF troops. This paper analyses the factors which facilitated and constrained Omani policy during the 20-year period and argues that Oman is only able to further its security interests when they are framed in a way that are conducive to the overriding political interests of the GCC.
Keywords: Vie politique -- Oman -- 1970-2020

Subjects of Stability: Understanding the stability of the Qaboos regime through the views and experiences of Omani students - Tersmette, Keye Simon (Leiden University, 2014)
Keywords: Vie politique -- Oman -- 1970-2020

Ibadism and Omani Nation-Building since 1970 - Valeri, Marc (On Ibadism, 2014)
Keywords: Vie politique -- Oman -- 1970-2020